(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. It is known that in clinical practice there are no specific neurophysiological tests for diagnosis of glaucoma; however, quite often neurophysiological examination reveals changes which are asymptomatic for a long time before the clinical manifestations, which is especially important for the early diagnosis of glaucoma. Purpose of the study is to make a dynamic analysis of visual evoked potentials in patients with primary open-angle glaucoma at different stages of the disease. Material and Methods: a comprehensive clinical and neurophysiological study of 186 patients (358 eyes) with the diagnosis of primary open-angle glaucoma and in patients whose diagnosis was a subject to confirmation. Results: Based on the analysis of the results of neurophysiological studies, visual evoked potentials in response to pattern and flash, we saw a statistically significant difference between the initial and advanced stages in terms of the latent period P100 (Z = 2.33; p-value = 0.028), the amplitude of peaks P100-N135 (Z = 3.50 p-value = 0.00046), the amplitude of peaks P100-N75 (Z = 2.04; p-value = 0.04); between the advanced and far-advanced stages in terms of the latent period P100 (Z = 3.08; p-value = 0.033). According to the other studied estimates of indicators of visual evoked potentials in response to pattern and flash we did not find any significant differences. Conclusion. Usage of neurophysiological study methods visual evoked potentials in response to pattern is necessary for confirmation of the diagnosis and stage of development of glaucoma during the early diagnosis and the choice of further tactics of treatment.